How can we measure the prioritization of strategies for transitioning to a circular economy at macro level? : a new approach - Guarnieri, Patricia (2022)
This paper aims to develop and validate a questionnaire to measure the prioritization of strategies to transitioning towards a circular economy and to compare different countries. We proposed a questionnaire based on a five-level ordinal scale to evaluate the 24 strategies of the circular economy under a set of ten criteria given technical issues, as well as social, environmental and economic dimensions of sustainability. Each strategy was defined and evaluated by the participants on the same scale, who are stakeholders involved in the transition towards a circular economy. The validation was conducted by two main procedures, including semantic validation through 17 experts from five countries and statistical validation by 347 survey respondents from 25 countries. The results show that the questionnaire seems a reliable and valid tool to analyze which circular economy strategies countries, regions and cities prioritize. Few studies have been conducted to validate instruments about the circular economy; they are focused at the micro level, (industry). Studies that validate measurement instruments regarding the circular economy at the macro level are lacking. This study is the first one to validate the circular economy instrument at the macro level. It can help researchers and practitioners from public and private sectors from a variety of organizations in proposing actions to enable the transition and create performance indicators.